2020
DOI: 10.1016/j.spinee.2020.05.541
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical contribution of spinal structures to stability of the lumbar spine—novel biomechanical insights

Abstract: BACKGROUND CONTEXT: The contribution of anatomical structures to the stability of the spine is of great relevance for diagnostic, prognostic and therapeutic evaluation of spinal pathologies. Although a plethora of literature is available, the contribution of anatomical structures is still not well understood. PURPOSE: We aimed to quantify the biomechanical relevance of each of the passive spinal structure trough deliberate biomechanical test series using a stepwise reduction approach on cadavers. STUDY DESIGN:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 34 publications
3
76
0
Order By: Relevance
“…Multiple clinical investigations have showed that congenital malformations of spine (including scoliosis, kyphosis, spina bifida, spondylolysis and Klippel Feil syndrome) 35,36 , accidental back injury or ligament injury [37][38][39] , occupational exposure (such as crane and car drivers, weightlifters, etc.) [40][41][42] could induce aberrant mechanical loading of lumbar spine, and finally lead to IVDD.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical investigations have showed that congenital malformations of spine (including scoliosis, kyphosis, spina bifida, spondylolysis and Klippel Feil syndrome) 35,36 , accidental back injury or ligament injury [37][38][39] , occupational exposure (such as crane and car drivers, weightlifters, etc.) [40][41][42] could induce aberrant mechanical loading of lumbar spine, and finally lead to IVDD.…”
Section: Discussionmentioning
confidence: 99%
“…The whole pipeline was further evaluated on 5 pathological cases, in addition to the five non-pathological cases from the training dataset. The 3D CT images were initially acquired as part of a previous study in our institution (Widmer et al, 2020a) with approval from local ethical authorities (BASEC Nr. 2017-00874).…”
Section: Evaluation On Pathological Fsusmentioning
confidence: 99%
“…2017-00874). The specimens selected for this project were excluded in Widmer et al (2020a) as they were classified as severely pathological by a medical professional. To evaluate the robustness of the pipeline, different lumbar spinal segments were included.…”
Section: Evaluation On Pathological Fsusmentioning
confidence: 99%
“…There are seven major ligaments constraining the spine components and limiting the range of motion (ROM) in all directions. Due to their elasticity, they passively help return the spine back to the neutral position [13,14]. These ligaments of the spine are the ligamentum flavum (LF), attached between the lamina of each VB; the anterior longitudinal ligament (ALL); the posterior longitudinal ligament (PLL), which works with the ALL along the consecutive VB; the intertransverse ligament (ITL), which connects the transverse processes; the interspinous ligament (ISL), which connects the opposing edges of the spinous processes; the supraspinous ligament (SSL), which connects the peaks of the spinous processes; and the capsular ligament (CL), which connects the circumferences of the joining articular facet joints [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The first three ligaments allow for flexion and extension of the spine, while keeping the bony parts in their correct alignment. The remaining four ligaments connect all the posterior elements of the VB [13,17].…”
Section: Introductionmentioning
confidence: 99%